Optimization problems and second order approximated optimization problems - Eugenia Duca; Dorel I. Duca (Journal of Numerical Analysis and Approximation Theory, 2010)
In this paper, a so-called second order approximated optimization problem associated to an optimization problem is considered. The equivalence between the saddle points of the lagrangian of the second order approximated optimization problem and optimal solutions of the original optimization problem is established.